Population-level, patient-reported outcomes: a case study regarding a public health intervention that involves patients with life-limiting illnesses - Daveson, Barbara; Blanchard, Megan; Clapham, Sabina; Draper, Kylie; Connolly, Alanna; Currow, David (Frontiers in Public Health, 2023)
To the Editorial Board, On behalf of the authorship team, I am delighted to submit (in response to the editorial team) the following original research paper to Frontiers in Public Health (Public Health in the Context of Life-Limiting Illnesses) for review: Population-level, patient-reported outcomes: A case study regarding a public health intervention that involves patients with life-limiting illnesses.The primary topic of our study is a public health intervention that intends to improve population-level outcomes using point-of-care, patient-reported outcomes. Dying and death are public health concerns, but little is known about public health interventions that target populations living with life-limiting illnesses. This gap makes it difficult to identify best-practice public health interventions for this population and to achieve public health objectives. We aim to help address this knowledge gap.To this end, we present a case study, informed by the Organization for Economic Co-operation and Development's (OECD) Best-Practice Public Health Framework, to describe coverage, effectiveness, and equity using mixed methods. Data from 2012−2022 were analysed.Our analysis reports increases in the number of deaths in the program increased (n= 16,358 to 32,421, +98.2%) and as a percentage of the population that might benefit from palliative care (14.8% to 25.1%). The median age of those admitted for palliative care across the country and the proportion of services participating in the program located in outer regional and remote areas of Australia (+5.4%) increased. Access by patients that experience the greatest socio-economic disadvantage decreased. Improvements in relation to moderate distress related to pain were identified. But, one in five instances of severe distress related to pain did not improve. We conclude that population-level, patient-reported outcome data are useful and necessary in addressing public health objectives in populations with life-limiting illnesses. Our application of the OECD's Framework helps to identify and describe a national intervention that may be transferred to other settings to address health promotion objectives.